Comparable Triglyceride Reduction With Plasma Exchange and Insulin in Acute Pancreatitis – A Randomized Trial - Gubensek, Jakob; Andonova, Milena; Jerman, Alexander; Persic, Vanja; Vajdic-Trampuz, Barbara; Zupunski-Cede, Ana; Sever, Nejc; Plut, Samo (Frontiers in Medicine, 2022)
Background and Aims. Both insulin and plasma exchange (PE) are used in hypertriglyceridemic acute pancreatitis (HTG-AP). Our aim was to compare the efficacy of both treatments. Methods. A randomized, parallel group study performed in a tertiary hospital in 22 HTG-AP patients with non-severe prognosis and triglycerides between 15-40 mmol/L. Patients were randomized to daily PE or insulin infusion until triglycerides were <10 mmol/L. Primary outcome was % reduction in triglycerides within 24 hours. Secondary outcomes were days needed to lower triglycerides <10 mmol/L, highest CRP and percentage of patients with a severe course of pancreatitis. Results. There was a trend toward a greater decrease in triglycerides within the first 24 hours in the PE group (67±17% vs. 53±17%, p = 0.07), but the absolute difference was modest (mean difference of 6 mmol/L (14% of initial value)). Triglycerides fell below 10 mmol/L in a median (IQR) of 1 (1-2) and 2 (1-2) days, respectively (p = 0.25). Secondary outcomes related to disease severity were also comparable: highest CRP 229 vs. 211 mg/L (p = 0.69) and severe course of pancreatitis in 2/11 cases in both groups (p = 1.0). Regarding treatment complications, there was one mild hypoglycemia and one allergic reaction during PE. Survival was 100% in both groups. Conclusions. There was no significant difference, but only a trend toward a greater decrease in triglycerides with PE, and the clinical course was also comparable. These results do not support universal use of PE in patients with HTG-AP. (ClinicalTrials.gov, NCT02622854)